Application of Accounting Information Systems on profitability in Bank Syariah Indonesia - Sinaga, Imelda; Suharsana , Yohannes; Tania, Elizabeth Lusi (Universitas Serang Raya, 2025)
The purpose of this study is to reveal the significant influence of AIS (Accounting Information System) in the form of total assets, working capital, earning after tax, net operating assets, capitalization and cost efficiency on Islamic banking ROE. The research location used Islamic banking with audited financial statements. The number of samples in this study 45 financial statements. Research methods using multiple linear regression with software EVIEWS with descriptive analysis, classical assumption test and regression test panel data. There is an effect of capitalization Information System and cost effisiency on ROE that Islamic banking can adapt to changes in the environment and show a high level of competitiveness, thereby increasing the dynamic character in which Islamic products and services based on profit sharing have higher income volatility by taking into account the efficiency of resources such as human resources, infrastructure, and technology, regulation, level of competition, and economic conditions. While there is no significant effect of Accounting Information System total assets, working capital, earning after tax, net operating assets on ROE this is because Islamic banks do more credit loss reserves where, if the era of negative interest rates still lasts a long time, they will face serious problems plus the quality of unproductive assets, operating in an unstable business environment during a pandemic, an income structure that is dominated by revenue sharing rather than cost-based income in Islamic banks can create higher volatility in the Income Statement and require more current assets than fixed assets